Salutogenesis: a framework for perinatal mental well being - Kelly, R.; Hauck, Yvonne; Thomas, S. (Cambridge Publishing, 2016)
The aim of perinatal parent education and support groups is to assist parents in the adaption to parenting before and after childbirth. One way to do this is to incorporate a focus on mental health/wellbeing promotion including relationships, informal and formal support structures, expectations of parenting, and stressors/concerns of parenting. One challenge in contemporary health promotion is addressing the influence of stress on parental mental health. With global rates of perinatal depression at 15 per cent, the influence of stress on early parental mental health/ wellbeing warrants urgent attention. Antonovsky’s Salutogenic model and Sense of Coherence concept is widely regarded internationally as a valid, theoretical framework within health care. This discussion paper argues why Antonovsky’s framework is well positioned as a perinatal parent education framework for promoting wellbeing.